Pressure effects on the hot-salt stress-corrosion cracking of titanium alloys - Chevrot, Thierry (Cranfield University, 1994)
Benefiting from good specific mechanical properties, exceptional oxidation resistance, and high temperature capability, Titanium Alloys are used in Gas Turbine Engines, especially in the early stages of the compressor. However they are subject to stresscorrosion cracking in the laboratory when subjected to stresses and contaminated with salts at elevated temperatures. The lack of in-service failures of titanium components due to Hot-Salt Stress-Corrosion Cracking (HSSCC) is not yet understood. The parameters influencing the HSSCC of titanium alloys (temperature, load, stress and temperature cycling, quantity and kind of salt, air velocity, water vapour or oxygen content of the atmosphere, composition, texture, and microstructure of the alloy, surtace conditions), cannot account for the lack of in-service failure. After an examination of the service conditions within a typical gas turbine engine compressor, it was considered that the high pressures prevailing may extend the life of titanium alloys subjected to HSSCC. This work used a unique high temperature, high pressure, servo-hydraulic facility in order to carry out hot-salt stress-corrosion testing on titanium alloy 1M! 834 at high pressure. The results obtained show that high oxygen partial pressures extend significantly the life of 1M! 834 subjected to HSSCC. Continuous thermogravimetric measurements both in oxidising and salt-corroding environments were carried out to study the kinetics of the hot-salt attack of IMI 834. Basic metallography revealed the formation of channels which extend deep into the metal during the initial stages of hot-salt-corrosion. Theoretical thermodynamic studies highlighted the role of alloying elements and vapour phase metallic chlorides in the mechanisms of the HSSCC of titanium alloys. A new model for the hot-salt stress-corrosion of titanium alloys is proposed. It is based on the establishment of a self sustaining cycle where vapour phase metallic chlorides act as hydrogen carriers and can diffuse quickly into the material through channels.